2022
DOI: 10.1177/26320770221099586
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Health-Smart Holistic Health Program: A CBPR Approach to Improve Health and Prevent Adverse Outcomes for Black Older Adults

Abstract: Black older adults experience poorer health and health-related outcomes than their non-Hispanic White counterparts. Novel, tailored strategies to promote health and prevent adverse health-related outcomes that are aligned with the preferences and values of Black older adults are needed given the limited effectiveness of “one-size-fits-all” approaches. The present study evaluated the impact of a 9-week, community-based participatory research-informed program called the Health-Smart Holistic Health Program for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The other purpose of this paper is to provide an example of a program (the Health-Smart Holistic Health Program for Black Seniors [HSHH]) that is informed by this new model and has helped improve the health and quality of life of Black older adults living in a low-income urban community. We do not report specifics on the results of this intervention in this paper as our focus is on the integration of radical healing and CBPR; results are published elsewhere (Tucker et al, 2022). The radical healing CBPR model enables intervention research by counseling psychologists that dismantles anti-Black racism and reduces health disparities by: (a) naming the racism inherent in such research; (b) naming the anti-Black racism that underlies health disparities; (c) involving members of target Black communities as experts in this naming and in making the aforementioned intervention research responsive to anti-Black racism and cultural sensitivity (i.e., responsive to cultural preferences, promoting of comfort, trust and respect, and promoting of empowerment of others with limited power); (d) being holistic by taking into account the social factors and systems (e.g., no bus transportation, unsafe neighborhoods, racial trauma, sexual abuse trauma) that impact target health behaviors and research participation; and (e) empowering communities with the skills, knowledge, and support needed to obtain policy changes that address the social and systemic barriers (e.g., racism, health care injustice) to their health, wellbeing, and dignity.…”
Section: Purpose Of This Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The other purpose of this paper is to provide an example of a program (the Health-Smart Holistic Health Program for Black Seniors [HSHH]) that is informed by this new model and has helped improve the health and quality of life of Black older adults living in a low-income urban community. We do not report specifics on the results of this intervention in this paper as our focus is on the integration of radical healing and CBPR; results are published elsewhere (Tucker et al, 2022). The radical healing CBPR model enables intervention research by counseling psychologists that dismantles anti-Black racism and reduces health disparities by: (a) naming the racism inherent in such research; (b) naming the anti-Black racism that underlies health disparities; (c) involving members of target Black communities as experts in this naming and in making the aforementioned intervention research responsive to anti-Black racism and cultural sensitivity (i.e., responsive to cultural preferences, promoting of comfort, trust and respect, and promoting of empowerment of others with limited power); (d) being holistic by taking into account the social factors and systems (e.g., no bus transportation, unsafe neighborhoods, racial trauma, sexual abuse trauma) that impact target health behaviors and research participation; and (e) empowering communities with the skills, knowledge, and support needed to obtain policy changes that address the social and systemic barriers (e.g., racism, health care injustice) to their health, wellbeing, and dignity.…”
Section: Purpose Of This Papermentioning
confidence: 99%
“…Detailed results of the HSHH Program have been published elsewhere (Tucker et al, 2022) and show that the program was successful at improving participants’ Body Mass Index, loneliness, physical health-related quality of life, and psychological quality of life from preintervention to immediate postintervention. These changes were maintained 3 months after the end of the program.…”
Section: Radical Healing Cbprmentioning
confidence: 99%
“…This research resoundingly indicates that Black men value their health [20][21][22][23] -a necessary precursor to health promotion engagement [24]. This valuing of health among Black men as a necessary precursor to engagement is underscored by the success of interventions implemented in culturally important community settings [25,26], such as barbershops [27]. Barbershops are a place of cultural significance for many Black men and have long been safe spaces for Black men to congregate and discuss important topics [28], such as health and health promotion.…”
Section: Barbershop-based Health Promotion Effortsmentioning
confidence: 99%
“…Surface-level structures (e.g., including an image of a Black man on recruitment materials) increase receptivity of the effort, whereas deep-level structures (e.g., intentionally aligning the effort with the values of Black men) increase cultural salience (Resnicow et al, 1999). A large body of literature has found that health-promotion efforts that attend to these structures have been successful in promoting health among non-White individuals (Tucker et al, 2016(Tucker et al, , 2017(Tucker et al, , 2022.…”
Section: The Need For Race-based Tailoring Of Health-promotion Effortsmentioning
confidence: 99%